2010
DOI: 10.2319/092809-537.1
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of orthodontic composites

Abstract: Results indicate that tested orthodontic bonding composites are suitable for clinical application, but that further studies using different test methods are needed for Transbond XT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 18 publications
2
36
1
1
Order By: Relevance
“…To date many studies focused on their physical properties, such as shear bond strength (Finnema et al, 2010), with less emphasis on RBDM biocompatibility, despite the proximity of their application site to the periodontal tissues which may cause inflammation of gingiva, oral mucosa and alveolar bone (Borra et al, 2009). Different studies, dealing with RBDM biocompatibility, are based on in vitro tests because of the ability to control the environment and cellular responses (Jagdish et al, 2009;Franz et al, 2003;Malkoc et al, 2010). According to the strategies for material testing, presented by Wataha (2012), the purpose of our study, was to determine in vitro material liability, the dynamics of any component release and the potential of released monomers to alter cell metabolism and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date many studies focused on their physical properties, such as shear bond strength (Finnema et al, 2010), with less emphasis on RBDM biocompatibility, despite the proximity of their application site to the periodontal tissues which may cause inflammation of gingiva, oral mucosa and alveolar bone (Borra et al, 2009). Different studies, dealing with RBDM biocompatibility, are based on in vitro tests because of the ability to control the environment and cellular responses (Jagdish et al, 2009;Franz et al, 2003;Malkoc et al, 2010). According to the strategies for material testing, presented by Wataha (2012), the purpose of our study, was to determine in vitro material liability, the dynamics of any component release and the potential of released monomers to alter cell metabolism and function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the cytotoxicity of orthodontic primers (D'Antò et al, 2009) and composites (Malkoc et al, 2010) has been demonstrated, but no research focus on the relationship between toxicity and monomers elution rate. Therefore, the purpose of our study was to assess the cytotoxicity of three conventional orthodontic composites, correlating their cytotoxic effects to the analysis of monomer elution before and after polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the leachable components from the resins, such as bisphenol A-diglycidyl dimethacrylate (Bis-GMA), triethylene glycol dimethacrylate, and urethane dimethacrylate (UDMA) found in a wide range of resins, have been shown to have a definite cytotoxic effect. 2,3 Because of the proximity of miniimplants to the gingiva and other oral tissues, a similar effect could occur in these tissues. 1,2 The behavior of resins is directly linked to their chemical formulation, and the release of 25% to 45% of the monomers, which are not converted into polymers after polymerization, 4,5 occurs when using the conventional irradiation method.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Because of the proximity of miniimplants to the gingiva and other oral tissues, a similar effect could occur in these tissues. 1,2 The behavior of resins is directly linked to their chemical formulation, and the release of 25% to 45% of the monomers, which are not converted into polymers after polymerization, 4,5 occurs when using the conventional irradiation method. 5 Therefore, residual monomers 6 may trigger discrete to moderate-or even severe-inflammatory reactions, 7 in addition to having a direct influence on the physical, mechanical, and biologic properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several studies have been carried out on orthodontic adhesives [18][19][20], there was little emphasis regarding the biocompatibility of temporary composites used for covering miniscrews. The aim of this study was to evaluate the cytotoxicity of light-polymerized temporary fillings used for orthodontic miniscrew covering.…”
Section: Introductionmentioning
confidence: 99%